2021
DOI: 10.4314/sajas.v50i5.13
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin E, an oil blend and L-Arginine on breast meat from broiler chickens

Abstract: The study examined the effects of supplementing vitamin E on the fatty acid profile and breast meat quality of broilers fed diets containing an oil blend and L-Arginine. Two hundred sixteen Cobb 500 one-day-old broilers were randomly allocated to six treatments, namely T1: 6% palm oil (control); T2: blend of 4% palm oil and 2% sunflower oil + 0.25% L-Arginine (positive control); T3: T2 with 20 mg/kg vitamin E added; T4: T2 with 50 mg/kg vitamin E added; T5: T2 with 100 mg/kg vitamin E added; and T6: T2 supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 42 publications
2
6
0
Order By: Relevance
“…(2009) showed that dietary supplementation with 100 mg/kg VE significantly affected the feed/gain ratio of broilers, which was consistent with the results of Khatun et al. (2020). However, Pitargue et al.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…(2009) showed that dietary supplementation with 100 mg/kg VE significantly affected the feed/gain ratio of broilers, which was consistent with the results of Khatun et al. (2020). However, Pitargue et al.…”
Section: Discussionsupporting
confidence: 88%
“…The results of this experiment are consistent with the above results. Other studies have shown that in broiler chickens, VE supplementation reduces drip loss and shear force (Li et al., 2009) and increases meat redness (Khatun et al., 2020). Our experiments did not yield the same results.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations